(untitled) (International Journal of Food and Nutritional Sciences, 2022)
E-learning programs are expected to influence a broad array of skills, and due to their potential to affect the educational system from pedagogy to curriculum their integration needs to be done at multiple levels of the educational system. Today the approach is no longer simply putting computers in the classroom and connecting to the Internet. Indeed, a critical area at the system level to highlight is the pedagogical aspects of technology as a tool for learning, integrated into all aspects teaching and learning. Technology should become a student’s intellectual partner, and the focus should be on how students learn with technology. It is expected that the most direct impact of e-learning would be on the learning achievement of students.